Aberrant DNA methylation profile of hepatitis B virus infection. Issue 1 (24th September 2018) - Jin, Jinglan; Xu, Hongqin; Wu, Ruihong; Niu, Junqi; Li, Shibo
Abstract : We aimed to study the aberrant DNA methylation profile associated with hepatitis B virus (HBV) infection and,  to identify key genes and pathways associated with the HBV infection stage. A total of 54 antiviral treatment‐naïve HBV‐infected patients and six healthy controls were included. Genome‐wide methylated DNA immunoprecipitation analysis was performed, as previously described, after which the chip data were preprocessed. Subsequently, Cytoscape software was used for the construction of a protein‐protein interaction network, and a database for annotation, visualization, and integrated discovery software was used to conduct functional enrichment analysis. A total of 711 794 CpGs were obtained after data quality control, among which 152 780, 113 814, 90 747, and 175 868 CpGs showed differential methylation in acute hepatitis B (AHB) vs control, total‐C vs control, CH1 vs CA1, and AHB vs total‐C, respectively. Furthermore, RIPK3, PRDM10, JUN, and SNAI1 were at the center of the four associated networks, respectively. Differential methylated genes differentially methylated in these four comparisons were significantly enriched with olfactory transduction; positive regulation of transport; negative regulation of protein amino acid phosphorylation (eg, JUN), phosphorylation, phosphorus metabolic process, and phosphate metabolic process; and programmed cell death, respectively. RIPK3, PRDM10, JUN, and SNAI1 as well as olfactory transduction, positive regulation of transport, negative regulation of phosphorylation, and programmed cell death are important for the transformation associated with HBV infection stage. Moreover, JUN may be involved in HBV infection, mainly via the negative regulation of amino acid phosphorylation. Highlights: 1. There were plenty of aberrant methylated CpGs in the HBV‐infected patients. 2. Methylation of RIPK3, PRDM10, JUN, and SNAI1 were important for HBV stage. 3. JUN negatively regulated amino acid phosphorylation in HBV infection.